Incentives and prosocial behavior - Roland Bénabou; Jean Tirole (Institute for the Study of Labor (IZA), 2005)
We develop a theory of prosocial behavior that combines heterogeneity in individual altruism and greed with concerns for social reputation or self-respect. Rewards or punishments (whether material or image-related) create doubt about the true motive for which good deeds are performed and this overjustification effect can induce a partial or even net crowding out of prosocial behavior by extrinsic incentives. We also identify settings that are conducive to multiple social norms and those where disclosing one's generosity may backfire. Finally, we analyze the choice by public and private sponsors of incentive levels, their degree of confidentiality and the publicity given to agents' behavior. Sponsor competition is shown to potentially reduce social welfare.
Keywords: D64; D82; H41; Z13; 330; altruism; rewards; motivation; esteem; crowding out; overjustification effect; identity; social norms; morals; greed; psychology; Altruismus; Leistungsmotivation; Prestige